1996
DOI: 10.1038/383447a0
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestin acts as a clathrin adaptor in endocytosis of the β2-adrenergic receptor

Abstract: The ability of a system to regulate its responsiveness in the presence of a continuous stimulus, often termed desensitization, has been extensively characterized for the beta2-adrenergic receptor (beta2AR). beta2AR signalling is rapidly attenuated through receptor phosphorylation and subsequent binding of the protein beta-arrestin. Ultimately the receptor undergoes internalization, and although the molecular mechanism is unclear, receptor phosphorylation and beta-arrestin binding have been implicated in this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
1,105
2
15

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 1,289 publications
(1,155 citation statements)
references
References 26 publications
33
1,105
2
15
Order By: Relevance
“…These findings are important, because they represent the first demonstration that GPCRs and arrestins are colocalized in neurons. Additionally, these studies support notions derived from previous in vitro studies that suggest that arrestins are involved in regulating the trafficking of GPCRs (Ferguson et al, 1996;Goodman et al, 1996). Whether arrestins regulate the internalization of 5-HT,, receptors or other 5-HT,, re-ceptor functions is currently under investigation.…”
Section: Discussionsupporting
confidence: 81%
“…These findings are important, because they represent the first demonstration that GPCRs and arrestins are colocalized in neurons. Additionally, these studies support notions derived from previous in vitro studies that suggest that arrestins are involved in regulating the trafficking of GPCRs (Ferguson et al, 1996;Goodman et al, 1996). Whether arrestins regulate the internalization of 5-HT,, receptors or other 5-HT,, re-ceptor functions is currently under investigation.…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, a dominant-negative mutant of arrestin-2 attenuated agonist-induced internalization in transiently transfected HEK-293 cells [26]. Subsequently, it was found that purified arrestin-2 bound directly to clathrin and clathrin-coated vesicles [39] and the domains of arrestin-2 that are essential for clathrin binding have been identified [38,39,57]. Recently, arrestin-2 has been shown to also interact with adaptor protein 2 (AP-2) [60], a protein that plays a critical role in the recruitment of clathrin and assembly of clathrincoated pits (Fig.…”
Section: Role Of Arrestins In 5-ht 2a Desensitization and Internalizamentioning
confidence: 99%
“…Similar to other GPCRs, phosphorylated β 2 ARs then bind with high affinity to β-arrestin, which fully uncouples receptors from G proteins [4] and also interacts with clathrin and adaptor proteins, thereby facilitating rapid receptor endocytosis [5,6]. Internalized receptors traffic through early endosomes, localizing with transferrin receptors [7] and rab5a [8] before returning to the cell surface (recycling).…”
Section: Introductionmentioning
confidence: 99%